2021
DOI: 10.1002/ece3.7174
|View full text |Cite
|
Sign up to set email alerts
|

The population genetics of nonmigratory Allen’s Hummingbird (Selasphorus sasin sedentarius) following a recent mainland colonization

Abstract: Allen's Hummingbird comprises two subspecies, one migratory (Selasphorus sasin sasin) and one nonmigratory (S. s. sedentarius). The nonmigratory subspecies, previously endemic to the California Channel Islands, apparently colonized the California mainland on the Palos Verdes Peninsula some time before 1970 and now breeds throughout coastal southern California. We sequenced and compared populations of mainland nonmigratory Allen's Hummingbird to Channel Island populations from Santa Catalina, San Clemente, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Seasonal movements among the hummingbirds in our study areas are therefore more complex than previously presumed. Overall, we present evidence of facultatively controlled migratory behaviour in Allen’s hummingbirds ( figure 1 ), while there is currently little conclusive genetic [ 46 ] or morphological [ 26 , 29 ] evidence of distinct subspecies. We therefore suggest that factors other than subspecies dynamics are primarily driving differences in seasonal movement patterns among populations of Allen’s hummingbirds.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Seasonal movements among the hummingbirds in our study areas are therefore more complex than previously presumed. Overall, we present evidence of facultatively controlled migratory behaviour in Allen’s hummingbirds ( figure 1 ), while there is currently little conclusive genetic [ 46 ] or morphological [ 26 , 29 ] evidence of distinct subspecies. We therefore suggest that factors other than subspecies dynamics are primarily driving differences in seasonal movement patterns among populations of Allen’s hummingbirds.…”
Section: Discussionmentioning
confidence: 72%
“…The migratory behaviours of Allen’s hummingbirds have changed over the past half century since the non-migratory subspecies ( S. s. sedentarius ) purportedly colonized mainland southern California [ 27 ]. Since the colonization of the mainland by this resident subspecies, non-migratory Allen’s hummingbirds expanded their range and it was postulated that the subspecies ranges did not overlap [ 27 , 45 , 46 ]. Our data demonstrate that this is false, as both migratory and resident Allen’s hummingbirds co-inhabit the same territory in our study area ( figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the expectation for the magnitude and direction of gene flow is unknown in C. anna , largely due to enigmatic movement patterns, a previous study suggested high gene flow between three California populations (Engeln, 2013). Another California hummingbird, Allen's Hummingbird ( S. sasin ), was found to have high gene flow among the mainland populations (Myers et al, 2021), potentially indicative of high overall levels of mobility in hummingbirds. If gene flow in C. anna is extremely high, we might expect signatures of selection caused by exposure to novel selective agents during range expansion to be present across the entire species rather than divergent between populations.…”
Section: Methodsmentioning
confidence: 99%